Parental attendance in two early-childhood training programmes to improve nurturing care: A randomized controlled trial - Martins, RC; Machado, AKF; Shenderovich, Y; Soares, TB; da Cruz, SH; Altafim, ERP; Linhares, MBM; Barros, F; Santos, IS; Murray, J (Elsevier, 2020)
Parent training programmes have significant potential to improve the quality of children's early environments and thereby their development and life-course outcomes. The aim of this study was to identify and explain the extent to which parents engaged in two group-based training programmes, offered to high-risk families enrolled in a randomized controlled trial study called PIÁ in Southern Brazil. The programmes were: (1) ACT: Raising Safe Kids, a 9-week programme aiming to reduce harsh parenting and maltreatment and improve positive parenting practices; (2) Dialogic book-sharing (DBS), an 8-week programme aiming to promote parental sensitivity and improve child cognitive development and social understanding. Of the 123 mothers randomly allocated to the ACT programme, 64.2% (n = 79) completed the course, and of 124 mothers allocated to DBS, 76.6% (n = 95) completed the course. After the interventions, mothers were very positive about the experience of both programmes but highlighted practical difficulties in attending. In adjusted regression analyses, only two variables significantly predicted ACT course completion (maternal age and distance between the intervention site and household); no significant predictor was found for DBS attendance. We conclude that although high completion rates are possible, there are important challenges to engaging parents of young children in training programmes, and practical difficulties occurring during training courses may be more important for attendance than baseline participant characteristics.